Vasos griegos en colecciones del siglo XIX en Portugal - Morais, Rui (2021)
In this brief text in honour of my dear friend Paloma Cabrera, three important collections gathered in the 19th century are approached. The first, assembled by João Allen, is the oldest collection that would have entered Portugal and was brought together by this collector as part of his Grand Tour to Italy. The second collection was brought together by Dom Manuel de Souza Holstein (1703-1759) and by his son, Dom Alexandre de Souza Holstein (1751-1803), both ambassadors in Rome, and would have entered our country shortly after the accession to the throne of D. Maria II, around 1834. The third and last collection, gathered in the second half of the 19th century, encompasses different acquisitions by Portuguese monarchs and represents a good testimony of the interest in Classical Antiquity of the monarchs of Casa de Bragança.